Implementasi Sistem Kredit Semester (SKS) di Madrasah Aliyah terhadap Karakter Religius pada Era Revolusi Industri 4.0 - Zainuri, Ahmad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
SKS learning has been implemented at Madrasah Aliyah Negeri (MAN) 3 Palembang since the 2015/2016 academic year. This learning model is an innovative effort to improve the quality of education. Apart from that, the application of credits at MAN 3 Palembang can be an alternative for MAN 3 Palembang students who are interested in entering accelerated classes and is also a form of service provided to students who have a diversity of talents, interests, and intelligence, as well as having a superior program which is mandatory for new students. Research This is field research with a case study approach. The data sources in this research are primary data obtained from informants or stakeholders directly involved in the implementation of SKS at MAN 3 Palembang and secondary data sources as supporting data. Data collection instruments in this research were non-participant observation, in-depth interviews, and documentation—data analysis using triangulation techniques. Research findings show that implementing the Semester Credit System (SKS) at MAN 3 Palembang in facing the Industrial Revolution 4.0 era has gone well. MAN 3 Palembang has facilitated student diversity in terms of learning speed, thus enabling them to complete their studies in varying amounts of time. In general, the design of the curriculum structure and SKS learning load refers to Minister of Education and Culture Regulation Number 59 of 2014 and can face RI4.0, where learning facilities are digital and website-based and are supported by effective communication between madrasah principals, teachers, and students, and are effective implementation of the dormitory program as one of the mainstays of student development in religious character development.